Intracranial complications of acute sinusitis in children: The role of endoscopic sinus surgery. (July 2018) - Kou, Yann-Fuu; Killeen, Daniel; Whittemore, Brett; Farzal, Zainab; Booth, Tim; Swift, Dale; Berg, Eric; Mitchell, Ron; Shah, Gopi
Abstract: Objective: To study the role of endoscopic sinus surgery (ESS) in the management of intracranial complications of children with acute rhinosinusitis Methods: Retrospective chart review at a tertiary care pediatric hospital Main outcomes: Demographics, intracranial complications, length of hospital stay (LOS), neurological sequelae, ESS, neurosurgical procedures Results: Twenty-four children with a mean age (SD) of 12.9 years (+/-3.2) with an intracranial complication(s) of acute rhinosinusitis were identified between 2005-2016. A total of 22 were included and 15 (68%) of these were males. The most common complications were: subdural abscess (n=10), epidural abscess (n=10), meningitis (n=5), intraparenchymal abscess (n=5), and cavernous sinus thrombosis (n= 2). Neurologic symptoms included headache (n=12), hemiparesis (n=5) and aphasia (n=3). Average length of stay was 16 (+/- 9.2) days. Average follow up was 7 (+/-5.6) months. One patient had residual seizures and 1 had recurrent rhinosinusitis. Aphasia and hemiparesis resolved in all patients within 1 year. Nineteen (86%) patients had ESS within 4 days of admission. Fourteen patients (63%) had a neurosurgical procedure, 6 (27%) required more than 1 neurosurgical procedure. Six patients (27%) had concurrent neurosurgical drainage and ESS. Four patients (17%) had neurosurgical procedure followed by ESS and 3 patients (13%) were treated only by a neurosurgical procedure. Patients who underwent ESS prior to a neurosurgical procedure had significantly less risk of needing a neurosurgical intervention (OR = .02, p < .01). There was a significantly higher proportion of neurosurgical patients with positive Strep anginosus cultures compared to the ESS only group (85.7% vs 37.5%, p = .02). Studies with larger patient populations are needed to determine the role of ESS in the management of intracranial complications of children with acute rhinosinusitis. Discussion: Early ESS may be associated with less need for neurosurgical procedures.